ISAK 335 : Impelementasi Pada Penyajian Laporan Keuangan Masjid Al Mujahidin Banjarmasin dan Yayasan At Taqwa Banjarmasin - Ash Sidratil Muntaha, Muhammad Mu'allimi; Ainun, Basyirah; Mahyuni; Fadhillah, Rizky (P3M Politeknik Negeri Banjarmasin, 2024)
A non-profit organization is an organization that does not seek profit. Mosques and foundations are non-profit organizations. As a non-profit organization, mosques or foundations can present financial reports in accordance with the standards set by the Indonesian Institute of Accountants (IAI), namely ISAK 335 concerning Presentation of Financial Statements of Non-profit Oriented Entities. This study aims to determine and implement the process of preparing financial reports on both entities by following the financial accounting standards cycle and its presentation guided by ISAK 335. The type of research is a descriptive qualitative research. The data is qualitative data in the form of interview data regarding the history and management structure and quantitative data in the form of asset lists and financial report records. The method of data collection is documentation and interviews. The results of this study indicate that the two entities have not presented financial reports in accordance with ISAK 335. Both organizations only have cash in and cash out records. The management also still hasn't done an asset inventory. After preparing the 2023 financial report on the Al Mujahidin Banjarmasin Mosque, it is known that there is a deficit of (Rp86,934,858), - and the total net assets are worth Rp1,213,151,642, - and the total cash and cash equivalents at the end of the period 31 December 2023 is worth Rp4,358,692. While the At Taqwa Foundation Banjarmasin is known that there is a deficit worth (Rp143,447,862), - and the total net assets are Rp5,039,225,155, - and the total cash and cash equivalents at the end of the period December 31, 2023 is Rp115,113,811.